The metal hoard from pile in Scania, Sweden : place, things, time, metals, and worlds around 2000 BCE - Vandkilde, Helle (Studies (Statens historiska museum (Stockholm, Sweden)) ;, 2017)
In 1864, a large metal hoard of copper, bronze and silver objects was discovered at Pile in the southern Swedish region of Scania. The hoard has been dated to the onset of the rich Nordic Bronze Age, and emerges as the earliest, finest and one of the largest of the Nordic sacrificial deposits of metalwork in or near water. The metal hoard from Pile in Scania, Sweden' provides the first detailed documentation, Scientific examination and historical interpretation of the assemblage. Around 2000 BCE the site of Pile was networked with places near and far in a manner that boosted the political economy of Southern Scandinavia, adding to an atmosphere of tensions and charge - and it made history. The chapters unfold as a 'history from beneath' beginning with place, Things and time and concluding with metals and the worlds that intersected in Pile at the threshold of the long Bronze Age.